2012
DOI: 10.1108/13664381211274362
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the implementation of innovative financing (IF) of infrastructure

Abstract: PurposeFailure to resolve Ghana's infrastructure deficit, coupled with inability of traditional financing methods to meet current infrastructure demand, have triggered recent studies to explore strategic issues underpinning innovative financing (IF) of infrastructure. The purpose of this study is to explore potential impediments inherent in IF tools available to Ghana.Design/methodology/approachThe empirical aspect of the investigation used structured interviews and a survey questionnaire to gather data from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 22 publications
8
68
0
Order By: Relevance
“…The study revealed some reasons for delayed payments to include poor planning and bureaucracy on the part of the employer. This confirms earlier studies by Fugah and Agyarkwa [2] and Badu et al [18] about untimely payment of certificate by clients. The survey indicated that cash flow is a major challenge based on the contractors experience in an interview.…”
Section: Financial Challengessupporting
confidence: 82%
See 2 more Smart Citations
“…The study revealed some reasons for delayed payments to include poor planning and bureaucracy on the part of the employer. This confirms earlier studies by Fugah and Agyarkwa [2] and Badu et al [18] about untimely payment of certificate by clients. The survey indicated that cash flow is a major challenge based on the contractors experience in an interview.…”
Section: Financial Challengessupporting
confidence: 82%
“…This confirms a study by Ofori-Kuragu et al [6] in which they mention among others, difficulty in accessing credit facilities by contractors. The results show a continuous trend of funding challenges as state earlier by Badu et al [18]. Internally generated fund (IGF) as a solution to financing public project seems very critical to the respondents.…”
Section: Source Of Fundingsupporting
confidence: 57%
See 1 more Smart Citation
“…The methodology of any study relies upon the philosophy underpinning the research (Dainty, 2007;Badu et al, 2012). Saunders et al (2012) asserted that there are several research philosophies available to the researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Ngowi et al (2006) described the globalisation of infrastructure developments and their financing. The impact of this trend has already driven procurement and participation changes in many parts of the developing world (Badu et al 2012). The construction of 'mega-projects' has seen a dramatic rise in multi-national construction effort in many parts of the world.…”
Section: Globalisationmentioning
confidence: 99%